Health-related quality of life of adult with Type 2 diabetes mellitus in rural area - Basir, Nur Fadhilah; Juni, Muhamad Hanafiah; Abdul Rahman, Hejar; Azman, Ahmad Zaid Fattah; Abd Rahman, Zairina; Mohd Rani, Mohd Dzulkhairi (Community Health Society Malaysia, 2016)
Introduction: Type 2 Diabetes Mellitus is one of chronic illnesses that affect patients’ quality of life. The aim of this study was to determine the HRQOL among Type 2 diabetes mellitus patients attending health clinics at Tampin district, Negeri Sembilan. Methodology: A cross-sectional study applying the Malay version SF-36 and structured validated questionnaires among Type 2 diabetes mellitus patients attending five health clinics at district of Tampin, Negeri Sembilan whose were selected using stratified sampling method. Data were analysed using SPSS version 21 of significant level α=0.05. Results: Response rate was 99.5% (430 patients participated).The mean age of the respondents was 57.5 (±8.88) years and the mean duration of having diabetes was 7 (±5.01) years. The mean score of all SF-36 health domains with exception of role emotional of respondents were significantly lower than that of the normal population scoring by Azman.(2003). Physical functioning (P<0.001), role physical (P<0.001), vitality (P<0.001), mental health (P<0.001), social functioning (P<0.001), bodily pain (P<0.001), and general health (P<0.001) were seven domains indicated lower than Malaysian norm. Conclusion: HRQOL of Type 2 Diabetes patients were lower than that of Malaysian general population in all SF-36 domains, with the exception of role emotional domain.